Applying nanotechnology to enhance the efficacy of quercetin in breast cancer cells - Tiburzi, Silvina Mabel (2024)
Quercetin (QUE), a flavonoid abundant in fruits and vegetables, is known for its diverse biological activities, including potential anticancer effects with limited toxicity to normal cells. Despite its promising properties for breast cancer treatment, QUE faces challenges such as low bioavailability and rapid metabolism in vivo. Nanotechnology-based drug carriers have emerged as a potential strategy to address these issues. We previously showed that QUE exerts antiproliferative effects in MCF-7 breast cancer cells, with an estimated IC50 of 75 µM. In this work, we further investigated free QUE mechanism of action in MCF-7 cells. Clonogenic assays indicated that QUE inhibited the colony formation after 48 h of incubation with concentrations below its IC50. In addition, annexin V/PI staining analysis confirmed that QUE (75 µM) increased the apoptotic cell population by 30% compared to the control after 48 h. Furthermore, intracellular oxidant levels were significantly elevated in QUE-treated MCF-7 cells, as measured by the fluorogenic probe 2′,7′-dichlorofluorescin diacetate. Next, QUE was loaded on magnetic iron oxide nanoparticles coated with polyethylene glycol (MAG@PEG), a nanocarrier previously studied and demonstrated to be non-toxic. The incorporation of QUE (MAG@PEG@QUE) was qualitatively confirmed by FTIR spectroscopy, while the loading capacity was determined by UV-visible spectroscopy. Cytotoxic studies performed in MCF-7 cells exposed to MAG@PEG@QUE at a concentration equivalent to free QUE (75 µM, 48 h) showed that MAG@PEG@QUE significantly reduced cell proliferation and viability, accompanied by increased apoptosis. Furthermore, MCF-7 cells incubated with MAG@PEG@QUE exhibited changes in actin cytoskeleton, characteristic of apoptotic cells. TEM images confirmed the apoptosis and revealed the presence of vesicles containing clusters of MAG@PEG@QUE within cell cytoplasm. Targeting of magnetic nanoparticles was achieved in the presence of a static magnetic field, which led to a high intracellular accumulation of magnetic nanoparticles and induced cell death in targeted areas, without affecting adjacent cells. In conclusion, these findings suggest that MAG@PEG@QUE exhibits antitumor effects comparable to free QUE. This nanosystem has the potential to improve the bioavailability and targeted delivery of QUE for breast cancer treatment.